2014
DOI: 10.1891/1946-6560.5.4.420
|View full text |Cite
|
Sign up to set email alerts
|

Building Men’s Engagement in Intimate Partner Violence Groups

Abstract: Group programs, which are generally preferred in treatment with violent partners, often have a high dropout rate. Engagement, however, can be an influential factor in program completion (Rondeau, Brochu, Lemire, & Brodeur, 1999) and in maintaining those aspects learned by the end of the program (Contrino, Dermen, Nochajski, Wieczorek, & Navratil, 2007). This article looks at the meaning given by men to the concept of engaging in an intimate partner violence (IPV) group. In our effort to understand enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…As the pool of research on IPV intervention programs has long indicated limited or mixed support for the effectiveness of IPV interventions at reducing abusive behaviors, substantial effort has been put forth to examine factors that inhibit the production of strong and positive intervention effects. Although participant engagement has been hypothesized to be influential in producing positive program effects (McMurran & Ward, 2010; Orford et al, 2009; Roy et al, 2014; Scott & King, 2007), limited research has focused on the factors associated with increased and decreased responsiveness to the treatment process (Babcock et al, 2004; Gondolf, 2004). The purpose of this exploratory study was to identify the key factors that facilitate men’s responsiveness to IPV intervention in a sample of 180 participants who completed an IPV intervention program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the pool of research on IPV intervention programs has long indicated limited or mixed support for the effectiveness of IPV interventions at reducing abusive behaviors, substantial effort has been put forth to examine factors that inhibit the production of strong and positive intervention effects. Although participant engagement has been hypothesized to be influential in producing positive program effects (McMurran & Ward, 2010; Orford et al, 2009; Roy et al, 2014; Scott & King, 2007), limited research has focused on the factors associated with increased and decreased responsiveness to the treatment process (Babcock et al, 2004; Gondolf, 2004). The purpose of this exploratory study was to identify the key factors that facilitate men’s responsiveness to IPV intervention in a sample of 180 participants who completed an IPV intervention program.…”
Section: Discussionmentioning
confidence: 99%
“…Intimate partner violence (IPV) intervention programs (also referred to as Batterer Intervention Programs) are the primary treatment strategy used for men who perpetrate violence against their intimate partners (Babcock et al, 2016; Cannon et al, 2016). In Canada and the United States, group-based programs implemented by community organizations/agencies are the predominant intervention approach used in rehabilitation efforts for perpetrators of IPV (approximately, 97% are served in group treatment; Babcock et al, 2016; Cannon et al, 2016; Roy et al, 2014). In general, research suggests that group-based interventions offer several advantages over other intervention types such as individual treatment and couples-based programs, including decreasing feelings of isolation, promoting sharing and openness, and encouraging help-seeking behaviors (Sternbach, 2001; Yalom & Leszcz, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a promising line of methodologically-sound ethnographic/qualitative research studies has emerged, that reinforces and adds to the MI findings. This new research, based in grounded theory, have been conducted by various investigators, in which male BIP clients were interviewed, primarily with open-ended questions, to find out more about their group experiences (McGinn, et al, 2017;Morrison et al, 2018;Morrison et al, 2019;Scott & Wolfe, 2000;Roy et al, 2013Roy et al, , 2014Roy et al, , 2015Silvergleid & Mankowski, 2006). What makes these findings so valuable is that they address these processes and delineate the facilitator's role in helping clients become engaged and motivated to change.…”
Section: Ethnographic Research In Bipsmentioning
confidence: 99%
“…The construct of engagement has been investigated in various psychotherapy and counseling groups (Corey et al, 2010; Morran et al, 2004), including those for IPV perpetrators (Chovanec, 2012; McGinn et al, 2017; Parra-Cardona et al, 2013; Roy et al, 2014; Taft et al, 2003). In one study (Rondeau et al, 1999), a primary reason given by IPV male perpetrators who dropped out of the group was that they did not feel engaged.…”
Section: Introductionmentioning
confidence: 99%